Nietzsche und die Weltanschauungsliteratur: Denkfiguren - Autorinszenierungen - Textformate - Beßlich, Barbara (Scientia poetica, 2021)
The study aims to demonstrate the significance of Friedrich Nietzsche for ›Weltanschauungsliteratur‹ (ideological literature) in the early 20th century. ›Weltanschauungsliteratur‹ adopts thematic elements of Nietzsche’s cultural criticism. Nietzsche’s habitus of the outmoded academic outsider becomes important for the writers’ self-staging. ›Weltanschauungsliteratur‹ closely observes Nietzsche’s combination of philosophical reasoning and literary writing and develops it further. Finally, the article examines exemplary ›Weltanschauungsliteratur‹ by Salomo Friedländer, Theodor Lessing, Rudolf Pannwitz, and Ernst Bertram.
Gesehen am 31.01.2022